Money and finance after the crisis critical thinking for uncertain times - Christophers, Brett 1971; Leyshon, Andrew; Mann, Geoff (Hoboken, NJ John Wiley & Sons, 2017)
"Money and Finance After the Crisis provides a critical multi-disciplinary perspective on the post-crisis financial world in all its complexity, dynamism and unpredictability. Contributions illuminate the diversity of ways in which money and finance continue to shape global political economy and society."--Provided by publisher.
Money and finance after the crisis : taking critical stock / Brett Christophers, Andrew Leyshon, and Geoff Mann -- From time-space compression to spatial spreads : situating nationality in global financial liquidity / Dick Bryan, Michael Rafferty and Duncan Wigan -- Financial flows : spatial imaginaries of speculative circulations / Paul Langley -- Making financial instability visible in space as well as time : toward a more Keynesian geography / Gary A. Dymski -- Banks in the frontline : assembling space/time in financial warfare / Marieke de Goede -- Undoing apartheid : from land reform to credit reform in South Africa / Deborah James -- Infrastructure's contradictions : how private finance is re-shaping cities / Phillip O'Neill -- The financialization of nature conservation? / Jessica Dempsey -- Financialisation of Singaporean banks and the production of variegated financial capitalism / Karen P.Y. Lai and Joseph A. Daniels.
Includes index.
Keywords: Global Financial Crisis, 2008-2009.; Banks and banking; Economic history -- 21st century